A study on the Therapeutic Efficacy of Olopatadine Hydrochloride in the Management of Allergic Conjunctivitis - Chowdhury, Md Abu Nayeem; Hossain, AKM Mosharrof; Chowdhury, MA Hashem; Chowdhury, Shakhawat Hossain (Medicine Today, 2010)
A prospective interventional study was conducted to see the efficacy and safety of a ophthalmic preparation olopatadine hydrochloride (0.1%) on 40 allergic conjunctivitis patients attended the out-patient department of Ophthalmology, Sylhet M.A.G. Osmani Medical College Hospital. One drop of ophthalmic solution was administered 12 hourly in each eye for 2 weeks. Scoring of hyperaemia, itching, tearing, and photophobia were estimated before and 2 weeks after administration of the drug. After 30 min. & 2 weeks of administration of drug adverse effects were assessed if there was any. The mean scores of hyperaemia, tearing, itching and photophobia were reduced after 2 weeks of treatment. The scores of hyperaemia, itching, tearing, photophobia were found to be lower compared to Day 0. This change was statistically significant (p < 0.001). Olopatadine appeared to reduce ocular signs and symptoms in Allergic conjunctivitis . Key words: Olopatadine hydrochloride; Allergic conjunctivitis; Hyperaemia; Tearing; Itching; Photophobia. DOI: 10.3329/medtoday.v22i1.5599 Medicine Today Vol.22(1) 2010. 15-19